Aboodh transform and the stability of second order linear differential equations - Ramdoss Murali; Arumugam Ponmana Selvan; Choonkil Park; Jung Rye Lee (Advances in Difference Equations, 2021)
Abstract In this paper, we introduce a new integral transform, namely Aboodh transform, and we apply the transform to investigate the Hyers–Ulam stability, Hyers–Ulam–Rassias stability, Mittag-Leffler–Hyers–Ulam stability, and Mittag-Leffler–Hyers–Ulam–Rassias stability of second order linear differential equations.